Determining Indicators of RIDA Framework for Entrepreneurial Success in Halal Tourism - Wibowo, Finantyo Eddy; Nadzri, Suhaila binti; Puad, Nooraimi binti Mohd (ITQAN: Journal of Islamic Economics, Management, and Finance, 2025)
Halal tourism has increased in several countries, both Muslim and non-Muslim countries. In line with that, research on halal tourism is also growing. However, research that focuses on the RIDA Framework on the Success of Halal Tourism Entrepreneurial is still very limited because this framework is relatively new. This study aims to identify indicators in the RIDA Framework that can support the success of halal tourism entrepreneurship. Literature study research data comes from the Scopus database. Data analysis uses the selected reporting item approach for systematic reviews and meta-analyses (PRISMA). The results of the PRISMA study have identified 16 indicators of entrepreneurial success and then grouped them into four determining factors according to the RIDA framework. In the end, this study proves that the determining indicators based on the RIDA framework are able to support the success of halal tourism entrepreneurship. The results of this study can be responded to by the Association of Entrepreneurs and Community Organizations that do business in the Halal tourism industry by increasing their contribution to the available indicators.